MEASUREMENT OF SLOTTED WAVEGUIDE ANTENNA ARRAY DIRECTIVITY PATTERNS - M. V. Snastin; M. S. Bebko (Научный вестник МГТУ ГА)
The waveguide-slotted antenna array (SWAA) near-field measurements were carried out in an anechoic chamber (AEC) with further far field conversion and the comparison with the results of numerical calculations and modeling were made. To obtain the antenna power parameters (gain) gain comparison method was chosen.